Felsőoktatás Kínában 3. : A mennyiség és a minőség ellentmondásai - Keczer, Gabriella (Közép-Európai Közlemények, 2016)
In a series of studies I analyze the past and present of Chinese higher education. The topic may be justified by the fact that up to now no comprehensive study has been published in Hungary about the long way China went along from the darkest years of communism to nowadays’ education. In this third and final paper I analyze the contradictions of quantity and quality. The enormous expansion of Chinese higher education has resulted in serious problems, such as the widening gap between the central regions and the periphery, between the rich and the poor as far as the accessibility to higher education is concerned. It has also affected the quality of faculty, research, teaching material and infrastructure. I analyze the Janus-face of Chinese higher education and the dichotomy of quality and quantity. I build my analysis on international literature and statistical data.